Smart Meter Power Disconnection: Utilizing IoT for Power Meter Electricity Cut-Off - Iskandar Hayat Mubarak, Khairulanwar; Mat Akir, Rohaida (Evolution in Electrical and Electronic Engineering, 2025)
The creation of an Internet of Things (IoT)-based Smart Meter Power Disconnection system is presented in this study. This innovative approach provides Tenaga Nasional Berhad (TNB) with a modern alternative to their conventional method of disconnecting the fuselink near the electrical meter to cut off the electricity supply. The proposed system enables TNB workers to control the power supply remotely using the Blynk app and the Durian Uno platform. By connecting their smartphones to Durian Uno, employees can toggle the power supply on or off with a simple command, eliminating the need for physical visits to customer premises. The system integrates a relay connected to the main power supply, which responds to commands from the Blynk app, ensuring seamless remote operation. The developed system was tested under various network conditions, demonstrating high reliability and responsiveness. Results indicate that power disconnection and reconnection commands are executed within seconds, providing a fast and efficient solution for TNB. The system successfully reduced the time and labor required for manual disconnection, lowering operational costs while improving service efficiency. Furthermore, its compatibility with mobile data allows operation from any location with network coverage, enhancing accessibility and convenience. This smart solution streamlines power management, optimizing TNB’s workflow while ensuring a more responsive and cost-effective approach to electricity supply control.